Crystal Structures of Human Glycerol 3-phosphate Dehydrogenase 1 (GPD1) - Ou, X.; Ji, C.; Han, X.; Zhao, X.; Li, X.; Mao, Y.; Wong, L.; Wong, L.; Rao, Z.
Homo sapiens L-a-glycerol-3-phosphate dehydrogenase 1 (GPD1)catalyzes the reversible biological conversion of dihydroxyacetone (DHAP)to glycerol-3-phosphate. The GPD1 protein was expressed in Escherichia coli, and purified as a fusion protein with glutathione S-transferase. Here we report the apoenzyme structure of GPD1 determined by multiwavelength anomalous diffraction phasing, and other complex structures with small molecules (NADC and DHAP)by the molecular replacement method. This enzyme structure is organized into two distinct domains, the N-terminal eight-stranded b-sheet sandwich domain and the C-terminal helical substrate-binding domain. An electrophilic catalytic mechanism by the 3-NHC 3 group of Lys204 is proposed on the basis of the structural analyses. In addition, the inhibitory effects of zinc and sulfate on GPDHs are assayed and discussed.
Keywords: L-A-GLYCEROL-3-PHOSPHATE DEHYDROGENASE 1; NAD-DEPENDENT DEHYDROGENASE; CRYSTAL STRUCTURE; CATALYTIC MECHANISM; DHAP ACCUMULATION